2015
DOI: 10.18267/j.aop.483
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Determinants of Investment Inflows into Transition Economies

Abstract: This article investigates the relationship between institutional quality and the level of investment inflows into post-communist countries. We attempt to empirically verify the argument that institutional determinants are essential in explaining the variation in investment inflows into transition economies after the demise of socialism in the early 1990s. The role of institutions is assessed using Economic Freedom indices provided by the Heritage Foundation. Consequently, to investigate the progress of institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Similarly, Julio et al (2013) assert that improved home institutions are likely to have a material effect on the FDI levels in Portugal while using more recent data, Donu -Janíčko (2015) concluded that the institutional impact on the levels of FDI appears to be generally weaker than it is stated in the existing literature. The macroeconomic conditions seem to play a more dominant role in the decision-making process of the investors.…”
Section: Fdi and Institutions In Retrospectivementioning
confidence: 98%
“…Similarly, Julio et al (2013) assert that improved home institutions are likely to have a material effect on the FDI levels in Portugal while using more recent data, Donu -Janíčko (2015) concluded that the institutional impact on the levels of FDI appears to be generally weaker than it is stated in the existing literature. The macroeconomic conditions seem to play a more dominant role in the decision-making process of the investors.…”
Section: Fdi and Institutions In Retrospectivementioning
confidence: 98%